Association between cagA and vacA genotypes and pathogenesis in a Helicobacter pylori infected population from South-eastern Sweden - Karlsson, Anneli (BioMed Central, 2012)
BACKGROUND: Chronic gastritis, peptic ulcer disease, and gastric cancer have been shown to be related to infection with Helicobacter pylori (H. pylori). Two major virulence factors of H. pylori, CagA and VacA, have been associated with these sequelae of the infection. In this study, total DNA was isolated from gastric biopsy specimens to assess the cagA and vacA genotypes. RESULTS: Variations in H. pylori cagA EPIYA motifs and the mosaic structure of vacA s/m/i/d regions were analysed in 155 H. pylori-positive gastric biopsies from 71 individuals using PCR and sequencing. Analysis of a possible association between cagA and vacA genotypes and gastroduodenal pathogenesis was made by logistic regression analysis. We found that H. pylori strains with variation in the number of cagA EPIYA motif variants present in the same biopsy correlated with peptic ulcer, while occurrence of two or more EPIYA-C motifs was associated with atrophy in the gastric mucosa. No statistically significant relation between vacA genotypes and gastroduodenal pathogenesis was observed. CONCLUSIONS: The results of this study indicate that cagA genotypes may be important determinants in the development of gastroduodenal sequelae of H. pylori infection. In contrast to other studies, vacA genotypes were not related to disease progression or outcome. In order to fully understand the relations between cagA, vacA and gastroduodenal pathogenesis, the mechanisms by which CagA and VacA act and interact need to be further investigated.